Study of Nutritional Status, Taste Perception, Energy and Macronutrients Intake of Canteen Food Among SMAN 104 East Jakarta Students - Hasanah, Dinda Fauziah; Nareswara, Anastu Regita (Politeknik Kesehatan Kemenkes Jakarta II, 2024)
Adolescent nutrition remains a significant issue in Indonesia. This study aims to describe the nutritional status, taste perception, energy, and macronutrient content of canteen food among students at SMAN 104 East Jakarta. Using a descriptive cross-sectional design, 85 samples were selected through simple random sampling. Data were collected via anthropometric measurements, taste perception questionnaires, and canteen food nutrient analysis. Chi-Square analysis was used to test the relationship between characteristics and taste perception. Results showed 78.8% of respondents had good nutritional status, with significant differences between genders and age groups. Taste perception was generally good (97.6%), varying by age but not significantly by gender. Macronutrient analysis revealed varying content, with some menus exceeding 30% of daily nutritional needs for lunch. Significant relationships were found between nutritional status and age (p=0.047) and gender (p=0.009). In conclusion, while most students have good nutritional status and taste perception, there is room for improvement in macronutrient balance in canteen menus. Keywords: nutritional status, taste perception, adolescents